Bibliometric Exploration of Publication Development in Entrepreneurship Education - Mardiani, Eri; Syamsulbahri, Syamsulbahri; Ilhamiwati, Mega; Surahmi, Mila; Cahyani, Lidya (West Science Journal Economic and Entrepreneurship, 2024)
This research presents a bibliometric exploration of publication development in entrepreneurship education, aiming to elucidate trends, research focuses, and emerging opportunities within the field. Entrepreneurship education has gained prominence as a crucial discipline in academia and practice, reflecting the growing recognition of entrepreneurship's role in economic and societal advancement. Through bibliometric analysis techniques, including citation analysis, keyword analysis, and visualization methods, a comprehensive examination of scholarly publications related to entrepreneurship education from 1977 to 2023 was conducted. The findings offer insights into publication metrics, such as citation counts, author productivity, and impact indices, providing a nuanced understanding of the scholarly landscape. Visualization of term networks and trends revealed dominant research themes, evolving concepts, and potential research directions within entrepreneurship education. Practical implications derived from this study inform educators, policymakers, practitioners, and other stakeholders about curriculum design, policy formulation, and program implementation strategies to foster collaboration, innovation, and excellence in entrepreneurship education research and practice.